Social assistance and the Brazilian Constitution: initial considerations A assistência social e a Constituição brasileira: reflexões iniciais - Vera Maria Ribeiro Nogueira (Semina: Ciências Sociais e Humanas, 1990)
Social Assistance is considered nowadays as part of the rights related to social security in the Brazilian Constitution presenting new positions and determinations that have not been sufficiently investigated. This study recovers the recent; history of social assistance, the polemics caused by its insertion in social security, its progressions and retrogressions, eventually presenting the current proposals of President Collor's government for this area. <A assistência social coloca-se hoje como um dos direitos relativos à seguridade social na Constituição brasileira, apresentando novos balizamentos e determinações ainda não suficientemente investigados. Este estudo resgata a história recente da assistência social, as polêmicas causadas pela sua inserção na seguridade social, os seus avanços e retrocessos e conclui apresentando as propostas e reformas atuais do governo Collor na área.